La Caída de Alfredo Stroessner y el ocaso del sultanismo - Andrew Nickson (Centre de Recherches sur les Mondes Américains, 2020)
This article examines the final phase of the regime of Alfredo Stroessner (1954-89) in Paraguay from 1982 onwards and uses the concept of sultanism in order to understand the nature of its overthrow. The first section examines the extent to which the characteristics of the regime during this period conform to those of sultanism, a form of personalised political control first identified by Max Weber. The second section offers an account of the decline of the regime, highlighting the stance adopted by major social actors during this period. The final section seeks to show that the concept of sultanism also helps in understanding the nature of this process of decomposition and eventual collapse of the regime.